Pengaruh Kepemimpinan Etis terhadap Kinerja Adaptif Pegawai: Peran Mediasi Etos Kerja pada Kantor Kecamatan Kairatu Kabupaten Seram Bagian Barat - Marcoroy Lekawael; Hendry Selanno; Hengky Virgo Richardo Pattimukay (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze the influence of ethical leadership on employees' adaptive performance with work ethic as a mediating variable in the Kairatu District Office, West Seram Regency. The research approach used is quantitative, associative with survey data collection with cross-section data types. The population used in this study were all employees of the Kairatu District Office, West Seram Regency, totaling 46 people. The sample is part of the number and characteristics possessed by the population. The sampling method is full sampling. Data were analyzed by path analysis. The results of the study concluded that ethical leadership was proven to have a positive and significant influence on the adaptive performance of employees in the Kairatu District Office, West Seram Regency, both directly and through work ethic as a mediating variable. In addition, ethical leadership also has a positive and significant effect on employee work ethic, which in turn directly improves their adaptive performance. This shows that ethical leadership not only encourages a high work ethic but also strengthens employees' adaptability in facing changes and challenges in the workplace.